2005
DOI: 10.1007/11526858_20
|View full text |Cite
|
Sign up to set email alerts
|

Dependable Coding of Fiducial Tags

Abstract: Fiducial tags can be recognised successfully and decoded by computer vision systems in order to produce location information. We term a system dependable if its observable results are predictable and repeatable. The dependability of such a vision system is fundamentally dependent on the scheme used to encode data on the tag. We show that the rotational symmetry common to many tag designs requires particular consideration in order to understand the performance of the coding schemes when errors occur. We develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The CRC-code distinguishes only between the remaining ambiguities and is variable with respect to this objective. Since it cannot be computed analytically (Rice et al, 2004), testing revealed that using the generator polynomial 0x8D (CRC-8-CCITT, (Moon, 2005)), no other than the 0-codeword must be excluded for ambiguities. We moreover assume a marker will not carry more than 60 bits and thus construct primitive RS codes over GF(16) = GF(2 4 ) = GF(q m ).…”
Section: Marker Identificationmentioning
confidence: 99%
“…The CRC-code distinguishes only between the remaining ambiguities and is variable with respect to this objective. Since it cannot be computed analytically (Rice et al, 2004), testing revealed that using the generator polynomial 0x8D (CRC-8-CCITT, (Moon, 2005)), no other than the 0-codeword must be excluded for ambiguities. We moreover assume a marker will not carry more than 60 bits and thus construct primitive RS codes over GF(16) = GF(2 4 ) = GF(q m ).…”
Section: Marker Identificationmentioning
confidence: 99%
“…The CircleTag can be further configured to control the relative proportions of the tag that are occupied by the bullseye and data rings, giving rise to four tag shapes which may contain either template or symbolic payloads. The symbolic payload can be configured to store an arbitrary amount of data using the rotational invariance abstraction (Rice et al, 2004). Figure 1 shows four example tags.…”
Section: Cantagmentioning
confidence: 99%
“…Tags, then, need to incorporate directionality; a problem not unique to cluster tagging. In fact the solutions proposed for the inner coding for individual tags are equally applicable here [11]. The essential principle is to use a rotationally-invariant inner code, with specific bits used to indicate direction.…”
Section: Determining the First Tag: Rotational Invariancementioning
confidence: 99%